Optical adhesive composition, optical cement and adhesive sheet
By combining acrylate copolymers and modified block copolymers, the problems of insufficient bonding strength and poor high-temperature stability of optical adhesives at low temperatures are solved, achieving high bonding strength and good high and low temperature creep recovery performance, which is suitable for foldable device screen modules.
Patent Information
- Application Number
- CN202511769995.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-01-23
AI Technical Summary
Existing optical adhesives have insufficient bonding strength at low temperatures and poor high-temperature stability, making it difficult to simultaneously meet the reliable bonding and folding reliability requirements of multilayer functional films.
By combining acrylate copolymers and modified block copolymers, the cohesive strength and adhesive strength of the adhesive are improved through double bond polymerization. Double bonds are introduced to improve copolymerization ability through nucleophilic addition reaction between isocyanate groups and carboxyl groups on the block copolymers, and styrene blocks are added to increase the bonding strength.
It achieves high bonding strength and good high and low temperature creep recovery performance, meeting the requirements of foldable device screen modules.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of optical adhesive, in particular to an optical adhesive composition, an optical adhesive and an adhesive sheet. BACKGROUND
[0002] As the core bonding material of the foldable device screen module, the optical adhesive (OCA) not only needs to realize the reliable bonding of multi-layer functional films, but also needs to have optical transparency and folding reliability to ensure the display effect and durability of the display module. Therefore, the optical adhesive not only needs to have optical transparency, high bonding strength and environmental aging resistance, but also needs to have good creep recovery performance.
[0003] In order to ensure the folding performance of the optical adhesive under low temperature conditions, the optical adhesive is required to have a low modulus, but too low modulus will lead to the decrease of the bonding strength of the optical adhesive and the poor high-temperature stability. At present, the bonding strength is improved by increasing the amount of polar monomer, but when the polar monomer is a hydroxyl or carboxyl monomer, the increase of the content of the polar monomer will lead to the increase of the hydrogen bond, easy gelation, and the existence of the carboxyl group will easily corrode other functional layers; if the polar monomer is a nitrogen-containing or heterocyclic acrylic ester monomer, the Tg is too high, which will lead to the significant increase of the low-temperature modulus and the poor low-temperature folding performance.
[0004] Therefore, the present application is proposed. SUMMARY
[0005] The present application aims to provide an optical adhesive composition. The adhesive sheet containing the optical adhesive composition of the present application not only has high bonding strength and high cohesive strength, but also has good high and low temperature creep recovery performance.
[0006] In order to achieve the above-mentioned purpose of the present application, the present application provides an optical adhesive composition, which comprises the following components by weight fraction: acrylate copolymer 70-90 parts modified block copolymer 10-30 parts crosslinking monomer 0.01-0.3 parts photoinitiator 0.01-0.1 parts silane coupling agent 0.1-1 parts, the sum of the weight fractions of the acrylate copolymer and the modified block copolymer is 100 parts; The modified block copolymer comprises a modified monomer and a block copolymer grafted and modified; the block copolymer comprises a styrene block and a (methyl) acrylate block containing a carboxyl group, and the modified monomer is an alkyl acrylate containing an isocyanate group.
[0007] Further, the preparation method of the modified block copolymer comprises: mixing and reacting the block copolymer with the modified monomer, so as to obtain the modified block copolymer, wherein the molar ratio of the isocyanate group in the modified monomer to the carboxyl group in the block copolymer is (1-1.1):1.
[0008] Further, the block copolymer is a triblock copolymer of styrene-(meth)acrylate-styrene.
[0009] Further, the modified monomer comprises at least one of isocyanate acrylate, isocyanate methacrylate.
[0010] Further, the acrylic ester copolymer contains 70-90 wt% of soft monomers, 5-10 wt% of long-chain monomers and 5-20 wt% of polar monomers, based on the total weight of the monomer components in the acrylic ester copolymer being 100 wt%.
[0011] Further, the long-chain monomer is (meth)acrylic acid alkyl ester with alkyl carbon atoms being 12-18.
[0012] Further, the long-chain monomer comprises at least one of (meth)acrylic acid dodecyl ester, (meth)acrylic acid hexadecyl ester and (meth)acrylic acid octadecyl ester.
[0013] Further, the soft monomer is (meth)acrylic acid alkyl ester with alkyl carbon atoms being 4-10.
[0014] Further, the soft monomer comprises at least one of 2-ethylhexyl acrylate, butyl acrylate, n-octyl acrylate and isodecyl acrylate.
[0015] Further, the cross-linking monomer is a multi-functional (meth)acrylate monomer.
[0016] The second aspect of the present application provides an optical glue containing the optical adhesive composition according to the first aspect of the present application.
[0017] The third aspect of the present application provides an adhesive sheet made of the optical glue according to the second aspect of the present application or containing the optical adhesive composition according to the first aspect of the present application.
[0018] Compared with the prior art, the present application has the following beneficial effects: (1) The optical adhesive composition of the present application improves the cohesive strength and bonding strength of the adhesive by adding a certain amount of acrylate copolymer and modified block copolymer, and the modified block copolymer and the acrylate copolymer can be polymerized through double bonds, so that the compatibility of the modified block copolymer and the acrylate copolymer is good, and there is no problem of small molecule migration, and the durability is good; the carboxyl-containing block copolymer is modified by using isocyanate-containing alkyl acrylate, the isocyanate group and the carboxyl group on the block copolymer are subjected to nucleophilic addition reaction, the alkyl acrylate is grafted to the side chain part of the block copolymer, the reaction is mild and fast, and the double bond can be effectively introduced into the block copolymer, thereby improving the copolymerization capacity; the modified block copolymer with styrene block is used to introduce the hard segment part into the adhesive, so as to increase the bonding strength and cohesive strength of the adhesive.
[0019] (2) The optical adhesive composition of the present application not only has high bonding strength and cohesive strength, but also has good high-low temperature creep recovery performance, which meets the requirements of foldable device screen module for optical adhesive sheet. DETAILED DESCRIPTION
[0020] The technical solutions of the present application will be described below in conjunction with specific embodiments, but those skilled in the art will understand that the following described embodiments are part of the embodiments of the present application, not all the embodiments, and are only used to illustrate the present application, and should not be regarded as limiting the scope of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0021] In the embodiments, the specific conditions are not specified, and the conventional conditions or the conditions recommended by the manufacturer are used. The reagents or instruments used are not specified by the manufacturer, and are conventional products that can be purchased on the market.
[0022] In the description of the present application, the term "(meth)acrylic acid" refers to any one of methacrylic acid, acrylic acid, or a combination of the two.
[0023] The first aspect of the present application provides an optical adhesive composition, which comprises the following components in parts by weight: acrylate copolymer 70-90 parts modified block copolymer 10-30 parts crosslinking monomer 0.01-0.3 parts photoinitiator 0.01-0.1 parts silane coupling agent 0.1-1 parts The sum of the weight parts of the acrylate copolymer and the modified block copolymer is 100 parts; The modified block copolymer is prepared by grafting modification of a modified monomer on a block copolymer; the block copolymer comprises styrene blocks and (meth)acrylate blocks containing carboxyl groups; and the modified monomer is alkyl acrylate containing isocyanate groups.
[0024] In the optical adhesive composition of the present application, by adding a certain amount of acrylate copolymer and modified block copolymer, the modified block copolymer and the acrylate copolymer can be polymerized through double bonds, thereby improving the cohesive strength and bonding strength of the adhesive; the modified block copolymer and the acrylate copolymer are compatible through bonding, and there is no problem of small molecule migration, and the durability is good; the alkyl acrylate containing isocyanate groups is used to modify and graft the block copolymer containing carboxyl groups, the isocyanate groups and the carboxyl groups on the block copolymer undergo nucleophilic addition reaction, the reaction is mild and fast, and the double bonds can be effectively introduced into the block copolymer, thereby improving the copolymerization ability; the modified block copolymer with styrene blocks is used to introduce the hard segment part into the adhesive, thereby increasing the bonding strength and cohesive strength of the adhesive.
[0025] In the specific embodiment of the present application, the preparation method of the modified block copolymer comprises: mixing and reacting the block copolymer and the modified monomer to obtain the modified block copolymer, wherein the molar ratio of isocyanate groups in the modified monomer to carboxyl groups in the block copolymer is (1-1.1):1. Controlling the molar ratio of isocyanate groups in the modified monomer to carboxyl groups in the block copolymer to be (1-1.1):1 can ensure that most of the carboxyl groups are grafted with the alkyl acrylate monomer containing isocyanate groups.
[0026] In a specific embodiment, the reaction temperature is 40-60°C, and the reaction time is 6-8 h.
[0027] In the specific embodiment of the present application, the block copolymer is a triblock copolymer of styrene-(meth)acrylate-styrene. The block copolymer can also use commercially available products, such as FBP-003 and FBP-004 produced by Fujikura Kasei Co., Ltd.
[0028] In the specific embodiment of the present application, the modified monomer comprises at least one of isocyanate acrylate (AOI) and isocyanate methacrylate (MOI).
[0029] In the detailed description of the present application, during the reaction, a certain amount of catalyst can be added to promote the rapid progress of the grafting reaction. The type of the catalyst is not particularly limited, and a conventional organotin catalyst can be selected, for example, including but not limited to dibutyltin dilaurate (DBTDL). The amount of the catalyst is not particularly limited, and can be adjusted according to the actual reaction speed and requirements, for example, the amount of the catalyst can be 0.1-0.5 parts by weight with respect to 100 parts by weight of the block copolymer.
[0030] In the detailed description of the present application, the acrylic ester copolymer contains 5-10 wt% of long-chain monomers, specifically 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, or any value between any two of the above values, based on 100 wt% of the total weight of the monomer components in the acrylic ester copolymer. Limiting the content of long-chain monomers to this range is beneficial to maintaining the balance between low modulus and bonding strength of the adhesive.
[0031] In the detailed description of the present application, the long-chain monomer is an alkyl (meth)acrylate with an alkyl carbon atom number of 12-18, specifically 12, 14, 16, 18, or any integer value between any two of the above values. Using an alkyl (meth)acrylate with an alkyl carbon atom number in the above range can effectively increase the free volume of the adhesive due to the long-chain structure of the monomer, thereby reducing the modulus. Further, the long-chain monomer includes at least one of lauryl methacrylate (LMA), lauryl acrylate, hexadecyl acrylate, hexadecyl methacrylate, octadecyl acrylate, and octadecyl methacrylate.
[0032] In the detailed description of the present application, the acrylic ester copolymer contains 5-20 wt% of polar monomers, specifically 5 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt%, 20 wt%, or any value between any two of the above values, based on 100 wt% of the total weight of the monomer components in the acrylic ester copolymer. Limiting the content of polar monomers to this range can improve the bonding strength of the adhesive. The content of polar monomers should not be too high, as too much polar monomer can easily lead to gel; otherwise, the improvement in the bonding strength of the adhesive will not be obvious.
[0033] In the detailed description of the present application, the polar monomer includes a hydroxyl-containing monomer. Further, the polar monomer includes at least one of 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate (HEMA), hydroxypropyl acrylate (HPA), and 4-hydroxybutyl acrylate (4-HBA).
[0034] In the specific embodiments of the present application, the acrylic ester copolymer further contains 70-90 wt% of soft monomers, specifically 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt% or any value between any two of the above values, based on the total weight of the monomer components in the acrylic ester copolymer being 100 wt%. Limiting the content of soft monomers within this range can reduce the glass transition temperature of the acrylic ester copolymer, which is conducive to reducing the modulus of the adhesive at low temperature.
[0035] In the specific embodiments of the present application, the soft monomer is an alkyl (meth)acrylate with an alkyl group having 4-10 carbon atoms. Further, the soft monomer includes at least one of 2-ethylhexyl acrylate (2-EHA), butyl acrylate (BA), n-octyl acrylate (OA) and isodecyl acrylate (IDA).
[0036] In the specific embodiments of the present application, the monomer conversion rate of the acrylic ester copolymer is 5%-10%, specifically 5%, 6%, 7%, 8%, 9%, 10% or any value between any two of the above values. Limiting the monomer conversion rate of the acrylic ester copolymer within this range in the present application avoids excessively high conversion rate, which leads to excessively high viscosity and is inconvenient for coating.
[0037] In the specific embodiments of the present application, the viscosity of the acrylic ester copolymer is 2,000-5,000 cps, specifically 2,000 cps, 3,000 cps, 3,500 cps, 4,000 cps, 5,000 cps or any value between any two of the above values. Limiting the viscosity of the acrylic ester copolymer within this range in the present application facilitates coating.
[0038] In the specific embodiments of the present application, the acrylic ester copolymer further includes an initiator for initiating polymerization of monomers. The amount of the initiator is 0.025-0.1 parts, specifically 0.025 parts, 0.05 parts, 0.06 parts, 0.08 parts, 0.1 parts or any value between any two of the above values, based on 100 parts by weight of the total weight of the monomer components in the acrylic ester copolymer.
[0039] In the specific embodiments of the present application, the type of the initiator is not particularly limited, and a conventional photoinitiator can be selected, such as any one or more of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2,2-dimethoxy-2-phenylacetophenone (photoinitiator 651) and (2,4,6-trimethylbenzoyl)-diphenyl phosphine oxide (TPO).
[0040] In the specific embodiments of the present application, a certain amount of chain transfer agent can also be added in the polymerization of the acrylic ester copolymer to control the degree of polymerization and molecular weight of the acrylic ester copolymer. The amount of the chain transfer agent is 0.01-0.1 parts based on 100 parts by weight of the total monomer components in the acrylic ester copolymer, and can be specifically 0.01 parts, 0.05 parts, 0.06 parts, 0.08 parts, 0.1 parts, or any value between any two of the above values.
[0041] In the specific embodiments of the present application, the chain transfer agent can be a thiol compound, including but not limited to dodecanethiol (PE1), 2-mercaptoethanol, etc.
[0042] In the specific embodiments of the present application, the acrylic ester copolymer can be prepared by conventional polymerization methods, such as UV light-induced polymerization. In a specific embodiment, the preparation of the acrylic ester copolymer comprises: mixing the monomer components, the chain transfer agent, and the photoinitiator uniformly under a protective atmosphere, and then exposing to an LED light source with an LED light intensity of 0.1-0.5 mW until the viscosity of the reactants reaches 2,000-5,000 cps and the monomer conversion rate reaches 5-10%, to obtain the acrylic ester copolymer.
[0043] In the specific embodiments of the present application, the weight average molecular weight of the acrylic ester copolymer is controlled at 800,000-1,000,000 g / mol, and the molecular weight distribution index is not particularly required, and can be selected between 2-5 in the present application.
[0044] In the specific embodiments of the present application, the amount of the acrylic ester copolymer is 70-90 parts based on 100 parts by weight of the sum of the acrylic ester copolymer and the modified block copolymer, and can be specifically 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, or any value between any two of the above values.
[0045] In the specific embodiments of the present application, the amount of the modified block copolymer is 10-30 parts based on 100 parts by weight of the sum of the acrylic ester copolymer and the modified block copolymer, and can be specifically 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or any value between any two of the above values.
[0046] Controlling the amounts of the acrylic ester copolymer and the modified block copolymer within the above ranges is beneficial to maintaining a good balance between the modulus, bonding strength, high-temperature retention, and creep recovery performance of the adhesive sheet.
[0047] In the specific embodiment of the present application, the optical adhesive composition further comprises a crosslinking monomer, and the content of the crosslinking monomer is 0.01-0.3 parts by weight, specifically 0.01, 0.1, 0.15, 0.2, 0.3 or any value between any two of the above values, based on 100 parts by weight of the acrylate copolymer and the modified block copolymer. The introduction of the appropriate amount of crosslinking monomer can increase the crosslinking density of the adhesive sheet, which is beneficial to improve the high-temperature retention and creep recovery.
[0048] In the specific embodiment of the present application, the crosslinking monomer can be a multifunctional (meth)acrylate monomer, preferably a (meth)acrylate monomer with a functionality of 2-6, such as 1,6-hexanediol diacrylate (HDDA) with a functionality of 2, trimethylolpropane triacrylate (TMPTA) with a functionality of 3, and polydi-pentaerythritol hexaacrylate (DPHA) with a functionality of 6. The crosslinking monomer can be at least one of the above.
[0049] In the specific embodiment of the present application, the optical adhesive composition further comprises a photoinitiator, and the content of the photoinitiator is 0.01-0.1 parts by weight, specifically 0.01 parts, 0.025 parts, 0.05 parts, 0.06 parts, 0.08 parts, 0.1 parts or any value between any two of the above values, based on 100 parts by weight of the acrylate copolymer and the modified block copolymer.
[0050] In the specific embodiment of the present application, the type of the photoinitiator can be selected from the types of the photoinitiators listed in the acrylate copolymer, which will not be repeated here.
[0051] In the specific embodiment of the present application, the optical adhesive composition further comprises a silane coupling agent, and the content of the silane coupling agent is 0.1-1 parts by weight, specifically 0.1 parts, 0.2 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts or any value between any two of the above values, based on 100 parts by weight of the acrylate copolymer and the modified block copolymer.
[0052] In the specific embodiment of the present application, the silane coupling agent can be conventional γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane, etc., or a commercially available product, such as KBM-403 produced by Japan Shin-Etsu Chemical Industry Co., Ltd.
[0053] In the present application, the preparation method of the adhesive is not limited, and the commonly used preparation method of the adhesive can be used.
[0054] The second aspect of the present application provides an optical adhesive comprising the optical adhesive composition of the first aspect of the present application.
[0055] The present application provides a preparation method of optical adhesive, comprising the following steps: mixing components in proportion, stirring uniformly, standing and defoaming, and then obtaining the optical adhesive to be coated.
[0056] It can be understood that, in order to facilitate production, transportation and sales, the optical adhesive of the present application only limits the composition of components and does not limit the existing form of components, i.e. the components can be mixed with each other or can be stored independently. The storage mode of mixing or independence can be selected according to the actual use time.
[0057] The third aspect of the present application provides an adhesive sheet made of the optical adhesive of the second aspect of the present application or containing the optical adhesive composition of the first aspect of the present application.
[0058] In the specific embodiment of the present application, the thickness of the adhesive sheet can be set to different thicknesses according to specific needs, for example, it can be 25-100 μm, and specifically it can be 25 μm, 30 μm, 40 μm, 50 μm, 80 μm, 100 μm or a value between any two end values.
[0059] The present application also provides an optional preparation method of the adhesive sheet, comprising the following steps: using double roller coating to coat the optical adhesive between the light release film and the heavy release film, and then obtaining the adhesive sheet through UV curing. The thickness of the release film can be freely selected according to actual needs and is not particularly limited, for example, it can be set to 25-100 μm, and specifically it can be 25 μm, 30 μm, 40 μm, 50 μm, 80 μm, 100 μm or a value between any two end values.
[0060] In the specific embodiment of the present application, the UV curing intensity is 3-15 mW / cm 2 , and the irradiation time is 5-10 min.
[0061] In actual use, the release film of the adhesive sheet of the present application is torn off, and the adhesive sheet is pasted between two components to be pasted.
[0062] The following specific examples are used to further illustrate the objects and advantages of the present application, but these examples should not be regarded as limiting the present application. In the following examples, 1 g represents 1 part by weight.
[0063] Example 1 I. Preparation of acrylate copolymer In an open reactor, 80 g of 2-ethylhexyl acrylate (2-EHA), 10 g of lauryl acrylate (LA), 10 g of 4-hydroxybutyl acrylate (4-HBA), 0.025 g of chain transfer agent PE1 and 0.05 g of photoinitiator 184 were put in, stirred and purged with nitrogen for 1 h, and then exposed to an LED light source with an intensity of 0.1 mW to obtain an acrylate copolymer with a viscosity of 3,500 cps, a monomer conversion of 5.6% and a weight average molecular weight of 852,589 g / mol.
[0064] wherein the viscosity is measured by a rotational viscometer; the monomer conversion is calculated by a drying weight loss method; and the weight average molecular weight is measured by gel permeation chromatography (GPC).
[0065] II. Preparation of modified block copolymer 100 g of block copolymer FBP-003 (Toray Fine Chemicals Co., Ltd., solid content 35%), 5 g of MOI and 0.1 g of DBTDL were put into a reaction vessel, stirred and reacted at 40°C for 6 h; and the solvent in the block copolymer was removed under reduced pressure at 50°C, thereby obtaining a modified block copolymer.
[0066] III. Preparation of adhesive sheet The acrylate copolymer prepared above 80 g, the modified block copolymer 20 g, the photoinitiator 184 0.05 g, the crosslinking monomer HDDA 0.1 g and the silane coupling agent KBM-403 0.3 g were mixed uniformly, defoamed by standing, to obtain an optical adhesive. The optical adhesive was coated between a release film and a heavy release film using a double roller coating, and irradiated with ultraviolet light at an intensity of 10 mW / cm 2 for 5 min to obtain an adhesive sheet with a thickness of 50 μm.
[0067] Example 2 This example was performed according to Example 1, except that the types or amounts of some components in the optical adhesive were different, and the rest were the same as in Example 1, as shown below: The raw materials for the acrylate copolymer were 2-EHA 70 g, LA 10 g, 4-HBA 20 g and photoinitiator 184 0.025 g. The acrylate copolymer had a viscosity of 5,000 cps, a monomer conversion of 6.7% and a weight average molecular weight of 811,035 g / mol; The block copolymer in the modified block copolymer was replaced by an equal amount of FBP-004 (Toray Fine Chemicals Co., Ltd., solid content 35%) instead, and the rest were the same as in Example 1; Optical adhesive raw material composition: prepared acrylate copolymer 70 g, modified block copolymer 30 g, photoinitiator TPO 0.025 g and crosslinking monomer DPHA 0.05 g.
[0068] Example 3 This example is carried out with reference to Example 1, the only difference being that the types or amounts of some components in the optical adhesive are different, and the rest are the same as in Example 1, the specific differences being as shown below: Raw material composition of acrylate copolymer: 2-EHA 90 g, LA 5 g, 4-HBA 5 g and photoinitiator 651 0.05 g, viscosity of acrylate copolymer 4,300 cps, monomer conversion rate 6.2%, weight average molecular weight 827,345 g / mol; Optical adhesive raw material composition: prepared acrylate copolymer 90 g, modified block copolymer 10 g, photoinitiator 184 0.1 g and crosslinking monomer HDDA 0.25 g.
[0069] Example 4 This example is carried out with reference to Example 1, the only difference being that the types or amounts of some components in the optical adhesive are different, and the rest are the same as in Example 1, the specific differences being as shown below: Raw material composition of acrylate copolymer: IDA 80 g, LA 10 g, HEA 10 g, viscosity of acrylate copolymer 4,600 cps, monomer conversion rate 6.4%, weight average molecular weight 832,840 g / mol; Optical adhesive raw material composition: photoinitiator 651 0.05 g, crosslinking monomer TMPTA 0.1 g.
[0070] Comparative Example 1 group This comparative example group is carried out with reference to Example 1, the only difference being that the amounts of acrylate copolymer and modified block copolymer in the optical adhesive are different, and the rest are the same as in Example 1, the specific differences being as shown below: Comparative Example 1a: acrylate copolymer 100 g, without modified block copolymer; Comparative Example 1b: acrylate copolymer 95 g, modified block copolymer 5 g; Comparative Example 1c: acrylate copolymer 60 g, modified block copolymer 40 g.
[0071] Comparative Example 2 This comparative example is carried out with reference to Example 1, the only difference being that 20 g of block copolymer FBP-003 is used in the optical adhesive instead of the modified block copolymer in Example 1.
[0072] Comparative Example 3 group The comparative example group was conducted in reference to Example 1, with the only difference being the amount of the components in the acrylic copolymer in the optical adhesive, and the rest being the same as Example 1, with the specific differences being shown below. Comparative Example 3a: 2-EHA 90 g, no LA, 4-HBA 10 g, viscosity of the acrylic copolymer 2,800 cps, monomer conversion rate 5.2%, weight average molecular weight 928,738 g / mol; Comparative Example 3b: 2-EHA 75 g, LA 15 g, 4-HBA 10 g, viscosity of the acrylic copolymer 4,200 cps, monomer conversion rate 6.3%, weight average molecular weight 893,824 g / mol.
[0073] Comparative Example 4 group The comparative example group was conducted in reference to Example 1, with the only difference being the amount of the components in the acrylic copolymer in the optical adhesive, and the rest being the same as Example 1, with the specific differences being shown below. Comparative Example 4a: 2-EHA 65 g, LA 10 g, 4-HBA 25 g, acrylic copolymer gel; Comparative Example 4b: 2-EHA 90 g, LA 10 g, no 4-HBA, viscosity of the acrylic copolymer 2,500 cps, monomer conversion rate 7.2%, weight average molecular weight 942,618 g / mol.
[0074] Performance test The adhesive sheets prepared in each of the examples and comparative examples were subjected to the following tests, and the test results are shown in Table 1.
[0075] (1) 180° peel strength test: The test was conducted in accordance with the international standard ASTM D3330 "Standard Test Methods for Peel Adhesion of Pressure-Sensitive Tape", a 300 mm x 25 mm sample was taken, and was attached to a glass panel, and after being left to stand at 23 ± 1℃, 50 ± 5% RH for 20 min, the average adhesion required to tear the sample from the panel was measured, and was expressed in gf / 25 mm.
[0076] (2) High temperature holding power test: The test was conducted in accordance with the international standard ASTM D3654 "Standard Test Methods for Shear Adhesion of Pressure-Sensitive Tape", a 24 mm x 24 mm sample was taken, and was attached to a stainless steel SUS panel, and the SUS panel with the attached sample was hung in an 80℃ oven, a 1 kg weight was hung below the sample, and the time when the sample fell from the surface of the SUS panel was recorded.
[0077] (3) Test of shear modulus and creep performance: tear off the release film on the surface of the adhesive sheet, stack several pieces of the adhesive sheet to a sample of 1 mm in thickness, and cut into a disc shape of 8 mm in diameter, and use a rheometer (TA Corporation, model: HR10) to measure the shear modulus, the measurement frequency is 1 Hz, the temperature is raised at a rate of 5℃ / min from-50℃ to 150℃, and the measured shear modulus value is recorded in kPa.
[0078] The rheometer is tested at-20℃, 25℃ and 60℃ respectively under shear mode, the normal stress is 1 N, the shear stress is 10 kPa, the shear time is 600 s, and the recovery time is 600 s.
[0079] Table 1 Test results of different examples and comparative examples
[0080] It can be known from the test results that the optical adhesive composition of the present application simultaneously introduces a certain amount of acrylate copolymer and modified block copolymer, the prepared adhesive sheet not only has high bonding strength and cohesive strength, but also has good creep recovery performance under low temperature and high temperature conditions, and can meet the actual use requirements.
[0081] It can be known from the test results of comparative example 1 that if the modified block copolymer is not added or the addition amount is low, the prepared adhesive sheet has low peeling force and the high-temperature creep recovery rate decreases, which does not meet the product use requirements; if the amount of the modified block copolymer is too high, the introduction of too much hard segment will cause the shear modulus of the adhesive sheet to be too high, the colloid is too hard, and the product is not convenient to fold.
[0082] It can be known from the test results of comparative example 2 that if the unmodified block copolymer is directly introduced, it cannot react with the acrylate copolymer, the molecular chain relatively slips under the action of high temperature or external force, which leads to the decrease of high-temperature holding force and the decrease of creep recovery rate.
[0083] It can be known from the test results of comparative example 3 that if the long-chain monomer is not introduced in the acrylate copolymer, the shear modulus of the adhesive sheet significantly increases; if too much long-chain monomer is introduced in the acrylate copolymer, the peeling force significantly decreases, which cannot meet the bonding requirements.
[0084] It can be known from the test results of comparative example 4 that if the polar monomer containing hydroxyl is not introduced in the acrylate copolymer, even if the modified block copolymer is used, the peeling strength and high-temperature holding force of the adhesive sheet are still low, and the creep recovery rate is also low; if the amount of the polar monomer in the acrylate copolymer is too high, the acrylate copolymer will appear gel, which cannot be used.
[0085] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, and are not intended to limit the present application; although the present application has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions recorded in the above embodiments can be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An optical adhesive composition characterized by, The optical adhesive composition comprises the following components by weight parts: an acrylate copolymer 70-90 parts a modified block copolymer 10-30 parts a crosslinking monomer 0.01-0.3 parts a photoinitiator 0.01-0.1 parts a silane coupling agent 0.1-1 parts, the sum of the weight parts of the acrylate copolymer and the modified block copolymer is 100 parts; wherein the modified block copolymer is prepared by graft modification of a modified monomer and a block copolymer; the block copolymer comprises styrene blocks and (meth)acrylate blocks containing carboxyl groups, and the modified monomer is an alkyl acrylate containing isocyanate groups.
2. The optical adhesive composition according to claim 1, wherein, The preparation method of the modified block copolymer comprises mixing and reacting the block copolymer and the modified monomer to obtain the modified block copolymer, wherein the molar ratio of isocyanate groups in the modified monomer to carboxyl groups in the block copolymer is (1-1.1):
1.
3. The optical adhesive composition according to claim 1 or 2, characterized in that, The block copolymer is a triblock copolymer of styrene-(meth)acrylate-styrene. And / or, the modified monomer comprises at least one of isocyanate ethyl acrylate and isocyanate methacrylate.
4. The optical adhesive composition of claim 1, wherein The acrylate copolymer contains 70-90 wt% soft monomers, 5-10 wt% long-chain monomers, and 5-20 wt% polar monomers, based on the total weight of the monomer components in the acrylate copolymer being 100 wt%; the long-chain monomer is an alkyl (meth)acrylate with an alkyl carbon atom number of 12-18.
5. The optical adhesive composition according to claim 4, wherein, The long-chain monomer comprises at least one of dodecyl (meth)acrylate, hexadecyl (meth)acrylate, and octadecyl (meth)acrylate.
6. The optical adhesive composition of claim 4, wherein The soft monomer is an alkyl (meth)acrylate with an alkyl carbon atom number of 4-10.
7. The optical adhesive composition according to claim 6, wherein The soft monomer comprises at least one of 2-ethylhexyl acrylate, isodecyl acrylate, n-octyl acrylate, and butyl acrylate.
8. The optical adhesive composition of claim 1, wherein, The crosslinking monomer is a multifunctional (meth)acrylate monomer.
9. An optical adhesive, characterized by, The optical adhesive composition comprises the optical adhesive composition according to any one of claims 1-8.
10. An adhesive sheet, characterized by comprising: The optical adhesive composition is made of or contains the optical adhesive composition according to any one of claims 1-8.